THE EFFECT OF SHAKER EXERCISE AND EFFORTFUL SWALLOW ON CHANGES IN THE DEGREE OF DYSPHAGIA IN PATIENTS WITH STROKE: CASE REPORT - Rina Audina; Arif Setyo Upoyo; Agis Taufik (International Journal of Biomedical Nursing Review, 2025)
Introduction: Stroke can cause various kinds of complications. One of the complications of stroke is dysphagia. Therefore, dysphagia management is necessary for stroke patients with dysphagia. Dysphagia management can be done by screening stroke patients with dysphagia and carrying out swallowing therapy with shaker exercise and effortful swallow. Purpose: This case study aims to evaluate the effect of shaker exercise and effortful swallowing on changes in the degree of dysphagia in patients with stroke. Methods: The method used is case study analysis based on nursing intervention with description analysis. The sample used was a dysphagia patient with a stroke. The instrument used to measure the degree of dysphagia is the Gugging Swallowing Screen (GUSS). Discussion: After the shaker exercise and effortful swallow intervention for 5 consecutive days in the morning and evening, there was a change in the degree of dysphagia from initially getting 4 which means a severe degree of dysphagia with a high risk of aspiration to 18 which means mild dysphagia with a low risk of aspiration. Conclusion: Shaker exercise and effortful swallowing can improve the degree of dysphagia in stroke patients.